Cambridge Grammar for IELTS Grammar reference and practice - Hopkins D. Diana (Cambridge Books for Cambridge Exams)
Do you want to be confident that you have covered all the grammar you will need for the IELTS test? Would you like to improve your listening skills at the same time? Cambridge Grammar for IELTS provides comprehensive coverage of the grammar needed for the test and gives you the chance to hear grammar being used in different situations, as well as offering plenty of test practice. Presents grammar in a listening context Contains clear and reliable grammar explanations with lots of examples Encourages analysis of the language Practises a range of IELTS test tasks from the Academic and General Training Reading, Writing and Listening papers